The Impact of Implementing Digital Marketing and Branding on Increasing Sales and Competitive Advantage of MSMEs (Case Study of MSMEs Fostered by PT. PHR) - Arif, Muhammad; Nosa, Muhammad Ridho; Triyono, Wahyu; Fadhillah, Ulva (Politeknik Negeri Bengkalis, 2024)
This study aims to analyze the effect of digital marketing and branding implementation on increasing sales andcompetitive advantage in MSMEs fostered by PT. PHR in Riau. Digital marketing includes the use of various onlineplatforms for promotion, while branding focuses on building a positive image and brand loyalty. The method used isquantitative research with multiple linear regression analysis techniques processed using SPSS 29 software. The resultsof the study show that branding has a more significant effect on increasing sales (62.8%) and competitive advantage(113.7%) compared to digital marketing, which only contributed 13% and 22.3% respectively. Prerequisite testsincluding normality, heteroscedasticity, and linearity tests show that the data used meets the criteria for statisticalanalysis. The main conclusion of this study is that MSMEs who want to increase their competitiveness in the digital eraneed to prioritize the development of branding strategies, although digital marketing remains an important component.This study provides practical implications for MSMEs in utilizing digital technology to improve their businessperformance.